2014
DOI: 10.1186/1752-153x-8-1
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and in vitroevaluation of the cytotoxic and antioxidant activities of supercritical carbon dioxide extracts of pitaya (dragon fruit) peel

Abstract: BackgroundHylocereus polyrhizus and Hylocereus undatus are two varieties of the commonly called pitaya fruits, and pitaya fruits have gained popularity in many countries all over the world. However, studies on chemical composition and the nutritional quality of pitaya flesh peel are limited.ResultsExtracts of pitaya (H. polyrhizus and H. undatus) peel were extracted by supercritical carbon dioxide extraction, and analyzed by gas chromatography–mass spectrometry analysis. Their cytotoxic and antioxidant activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
122
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(159 citation statements)
references
References 26 publications
3
122
1
9
Order By: Relevance
“…Apart from its composition, a study of B16F10 melanoma cancer cells revealed that the peel of dragon fruit has a stronger antiproliferative effect than the pulp [4]. Furthermore, a recent study showed that extracts of dragon fruit peel obtained using supercritical fluid extraction had good cytotoxic activity against PC3, Bcap-37 and MGC-803 cells, with IC 50 values ranging from 0.61 to 0.73 mg/mL [6].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Apart from its composition, a study of B16F10 melanoma cancer cells revealed that the peel of dragon fruit has a stronger antiproliferative effect than the pulp [4]. Furthermore, a recent study showed that extracts of dragon fruit peel obtained using supercritical fluid extraction had good cytotoxic activity against PC3, Bcap-37 and MGC-803 cells, with IC 50 values ranging from 0.61 to 0.73 mg/mL [6].…”
Section: Introductionmentioning
confidence: 97%
“…However, various studies have shown that dragon fruit peel is a potential source of natural functional food ingredients [1,[6][7][8]. Dragon fruit peel primarily consists of pectin (10.79%), betacyanin pigments (150.46 mg/100 g db) and up to 69.30% total dietary fiber [1].…”
Section: Introductionmentioning
confidence: 99%
“…One of the candidates is dragon fruit peel which is not generally utilized. The dragon fruit peel is potential as a natural colorant (Harivaindaran et al, 2008), an antibacterial against nine bacteria of food pathogen (Nurmahani et al, 2012), and natural antioxidant (Luo et al, 2014). The addition of red dragon fruit peel extracts were expected to give better characteristics based on color, antioxidant, and antibacterial on beef sausage.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, extraction technique i.e., supercritical fluid extraction (SFE) and solid phase microextraction (SPME) coupled with above detectors are used for essential Oil purpose [21], But, time consuming and low sensitivity are main issues. In fact, GC-MS is the best and useful method for the Essential Oil determination and quantification due to its simplicity, rapidity and efficiency [22][23][24][25]. Also, GC-MS with fingerprint criteria have been shown reliable information for the essential Oil components that will be useful for medicine aspects [20].…”
Section: Introductionmentioning
confidence: 99%